A Novel Subfoveal Perfluorocarbon Liquid Removal Technique Combining a 25-Gauge Retrobulbar Needle With a Built-in 30-Gauge Needle - Yang, Yuan; Xiao, Haodong; Zhang, Xuerui; Mi, Wei; Wang, Xiaohan; Ye, Hongfei; Wen, Yanjun; Peng, Jie; Zhao, Peiquan (Frontiers in Medicine, 2022)
Introduction: To report a novel combining a 25-gauge retrobulbar needle with a built-in 30-gauge needle surgical technique for subfoveal perfluorocarbon liquid (PFCL) removal. Materials and Methods: Fourteen eyes of 14 patients who underwent subfoveal PFCL removal with a 25-gauge retrobulbar needle combined with a built-in 30-gauge needle were studied. The 30-gauge needle was inserted into the 25-gauge retrobulbar needle. The bent tip of the built-in 30-gauge needle was used to create a 30-gauge retinotomy at the farthest edge of the subfoveal PFCL droplet. Then, a flute cannula was used to aspirate the PFCL through the previously created retinotomy. The best-corrected visual acuity (BCVA) was determined, previous surgical history and postoperative complications were recorded. Results: Fourteen cases were analyzed. Most eyes (92.85%) showed an improvement in BCVA after surgery. The mean change in the BCVA was -0.7±0.72 logarithm of the minimum angle of resolution (logMAR) units (p=0.006). Postoperative complications included a self-healing macular hole in 1 eye and vitreous hemorrhage in 1 eye. Postoperative optical coherence tomography confirmed removal of the subfoveal PFCL with restoration of the macular fovea. Conclusions: Combining a 25-gauge retrobulbar needle with a built-in 30-gauge needle to remove subfoveal PFCL is easy to perform and carries little potential risk of subretinal impairment. This method also provides relatively good macular contour with functional improvement.